Medical phone book - Kan, Javier Hon Lum. (2012)
It is not uncommon to see medical students flipping through thick medical books and journals in search of a medical symptom or condition. Physicians were overwhelmed with tremendous amount of information. It’s impossible for them to memorize every single detail in the book. Thus, past generations of clinicians had equipped themselves with compact medical handbooks available. Searching through the wall of text in medical publications for the right contents to focus on had always been a problem.